2018
DOI: 10.14236/ewic/hci2018.215
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Texts and Drawings: The Teenage Perspective on Enjoyable Museum Experiences

Abstract: The contribution of this paper is centred around the qualitative data research conducted from several co-design sessions deployed with 155 teenage participants aged 15-19. The participants were asked to ideate a mobile museum experience that they would enjoy by writing and drawing about it. For this paper, we go over the thematic analysis applied to the results gathered as well as reporting the challenges faced and our attempts to overcome them. However, this work is still preliminary and will make use of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Participants' writing was transcribed while graphic elements were coded. Text and graphics were brought together in the same data set to identify the categories and themes emerging from what the teenagers considered to be enjoyable, interactive apps for museums (details in [13]).…”
Section: Co-designing With Teenagersmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants' writing was transcribed while graphic elements were coded. Text and graphics were brought together in the same data set to identify the categories and themes emerging from what the teenagers considered to be enjoyable, interactive apps for museums (details in [13]).…”
Section: Co-designing With Teenagersmentioning
confidence: 99%
“…The results of the co-design sessions (see [13,14,16]) suggested that teenagers particularly appreciate mobile experiences that include novel technologies, in particular Augmented Reality (AR) and Virtual Reality (VR); they are also keen to share their experiences via social media; they favor options for different tours to engage with different content; and suggest a mix of stories and games (they proposed games with treasure-hunts, competition, timeout and collection strategies; and stories that give the opportunity to become protagonists of the experience, engage directly with the exhibits and connect to it emotionally when possible). All these elements that emerged as important in the creative phase were taken into account in the design phase discussed next.…”
Section: Co-designing With Teenagersmentioning
confidence: 99%
“…According to formal studies about teenage preferences regarding museum engagement, Cesário et al [8,9] identified that teenage audiences particularly appreciate mobile experiences that include 1) Gaming and storytelling aspects, 2) Interaction elements, 3) Social media connections, and 4) Museum and exhibits relevant information. To contribute in filling in the gap regarding teenage engagement in museums, we designed the Memories of Carvalhal's Palace dual experience, geared towards better understanding teenagers' preferences and needs in museum contexts.…”
Section: Features On Enjoyable Museum Experiences For Teenagersmentioning
confidence: 99%
“…According to formal studies about teenage preferences regarding museum engagement, Cesário et al [29], [30] identified that mobile experience for museum's teenage audiences should first and foremost include 1) Gaming and storytelling aspects, secondarily teens look for 2) Interaction elements, 3) and Social media connections and last but not least 4) Museum and exhibits relevant information. Based on these findings and in accordance with the museum goals, the authors in collaboration with a team of creatives and developers, designed Memories of Carvalhal's Palace -Haunted Encounters, an interactive mobile game experience, engaging teens in solving a mystery thorough exploring the museum and its embalmed species collection.…”
Section: Gaming As a Strategy To Involve Teens In Museum Experiencesmentioning
confidence: 99%